The many paths for an open, participatory, and inclusive science - Campos, Rita (Septentrio Conference Series, 2023)
Watch VIDEO. Societies are facing unprecedented challenges due to human-induced climate change. In order to understand, cope with and halt global warming, we need to understand the science behind its causes and impacts and to identify reliable sources of information. Science and scientists play a crucial role in this process and are called to the forefront of new relational practices for engaging the public and helping citizens develop scientific competences to participate in contemporary societies. Empowering individuals with sustainable-oriented knowledge, skills and values is vital for an active citizenship towards sustainability. Moreover, promoting dialogic channels between science and society encourages a more critical view of current challenges and science-oriented attitudes. Participatory methodologies can play an essential role in this context as they entail the inclusion of citizens in research and/or knowledge production and a closer contact with local and global realities. I will discuss different paths taken in national and international research projects to promote the inclusion of citizens in science. I will focus on two examples. One related to how citizen science can be used in educational contexts to reconfigure schools as collaborative ecosystems, part of a network that connects teachers, students, and scientists, who share the responsibility to identify problems, think about possible solutions, reflect on existing knowledge, collect new evidence, and integrate different perspectives. Results show positive impacts on a personal and academic level, with participants declaring higher self-esteem and a deeper understanding of the scientific process and social and environmental issues. A second example concerns dialogical and arts-based strategies to include academic, political, and activist stakeholders in the public debate on the opportunities and challenges of biotechnology. These strategies are framed within a concept of engaged citizen social science, considering that engagement with science should be bidirectional, where both scientists and the public are committed to establishing an effective dialogue between different forms of knowledge to co-create new meanings and impacts for project outcomes. It is also rooted in interdisciplinary dialogues through interaction between the disciplinary fields of the partners and the individuals involved in the social dialogue to create a shared vocabulary and contribute to a transformative impact of the project on social realities. The planned art-based approaches to science will help facilitate participation through more dynamic, creative, and meaningful engagement and greater understanding of different worldviews, thoughts, and understandings. Preliminary results suggest a greater awareness of the different dimensions related to the development and (unanticipated) impacts of new technology by the scientists and the artists involved in this co-creation process.